Microelectronic systems 2: a practical approach - Dicth, W. (Great Britain : Edward Arnold, 1995)
This book covers objectives from the BTEC unit Microelectronic Systems (U86/333) at level NIII.
1. Microprocessor Based Systems -- 2. Memory Devices -- 3. The Stack and Interrupts -- 4. Microprocessor Support ICs -- 5. Trends in Microprocessor Design -- 6. Principles of System Design -- 7. Practical Applications -- 8. Integrative Assignments -- 9. GNVQ and Core Skills -- 10. Answers to Problems.
Includes index.
Keywords: MICROELECTRONICS